Fixing device and electrophotographic image forming apparatus
The fixing device with a PFA surface layer and spherulites addresses chemical cracks and abrasion issues, ensuring long-term high-quality image production in electrophotographic devices.
Patent Information
- Application Number
- JP2023104714
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2025-01-16
AI Technical Summary
The occurrence of chemical cracks in the surface layer of fixing films used in electrophotographic image forming devices due to the adherence of fluorine oil, which disrupts the molecular bonds of fluororesin, and the insufficient abrasion resistance of existing surface layers in film fixing devices.
A fixing device with a fixing film structure comprising a base layer, an elastic layer, and a surface layer made of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) with a plurality of spherulites, where the surface layer has an endothermic heat absorption of 21 J/g or more, and the orientation of PFA molecules is minimized to reduce crack formation.
The solution enhances the durability of the fixing device by significantly reducing chemical cracks and improving abrasion resistance, allowing for the formation of high-quality electrophotographic images over an extended period.
Smart Images

Figure 2025004852000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fixing device and an electrophotographic image forming apparatus. [Background technology]
[0002] Fixing members used in the heat fixing devices of electrophotographic image forming apparatuses such as printers, copiers, and facsimiles are available in the form of films or rollers. As such fixing members, there are known fixing members in which an elastic layer made of heat-resistant rubber or the like is formed as necessary on a film- or roller-shaped substrate made of heat-resistant resin or metal, and the surface layer of the fixing member contains a fluororesin having excellent releasability against toner. Here, as the fluororesin contained in the surface layer, a tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), which has excellent heat resistance, is preferably used.
[0003] Meanwhile, in recent years, from the viewpoint of promoting energy saving, a fixing device of a film heating type that heats via a fixing film with a small heat capacity, that is, a film fixing device, has been proposed as an on-demand method with high heat transfer efficiency and fast start-up of the device.Patent Document 1 and Patent Document 2 disclose that the film fixing device has, as a fixed and supported heating body, for example, a ceramic heater (hereinafter referred to as heater), as a heat transfer member that slides with the heater, for example, a heat-resistant resin film (hereinafter referred to as fixing film), and as a pressure member that is in pressure contact with the heater via the fixing film to form a fixing nip portion as a toner image heat fixing area, an elastic pressure roller as a pressure member, and a recording material carrying an unfixed toner image is sandwiched and conveyed between the fixing film and the pressure roller in the fixing nip portion, and the unfixed toner image is heated, melted, and fixed on the recording material by heat from the heater via the fixing film.
[0004] Incidentally, in a fixing device, as described in Patent Documents 3 and 4, in order to ensure sliding properties between the fixing film and a member arranged inside the fixing film so as to abut against the inner surface of the fixing film, a lubricant containing fluorine oil may be interposed between the fixing film and the member. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 63-313182 [Patent Document 2] Japanese Patent Application Publication No. 2-157878 [Patent Document 3] JP 2007-187889 A [Patent Document 4] JP 2005-84225 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the study by the present inventors, when the fixing device is in operation, a lubricant containing fluorine oil may adhere to the surface layer of a fixing film having a surface layer containing a fluorine resin such as PFA. At this time, cracks may occur in the surface layer along a direction perpendicular to the circumferential direction of the fixing film. For the surface layer containing fluorine resin, a fluorine resin tube formed by extruding fluorine resin into a cylindrical shape is often used. In such a fluorine resin tube, the fluorine resin is crystallized by the molecules of the fluorine resin oriented in a direction perpendicular to the circumferential direction. The present inventors consider that the cracks are caused by the fluorine oil penetrating between the molecules of the fluorine resin oriented in a direction perpendicular to the circumferential direction and loosening the bonds between the molecules of the fluorine resin. Hereinafter, the cracks in the surface layer at the adhesion points of the fluorine oil are also called "chemical cracks".
[0007] On the other hand, it has been found that the occurrence of chemical cracks is suppressed in a surface layer formed by melting fluororesin particles attached to an elastic layer, or in a surface layer in which the orientation of the fluororesin is relaxed by heating a fluororesin tube on the surface layer to a temperature equal to or higher than the melting point of the fluororesin. However, although the surface layers obtained by these methods can suppress the occurrence of chemical attacks, there is room for improvement in terms of abrasion resistance.
[0008] At least one aspect of the present disclosure is directed to providing a fixing device that contributes to the formation of high-quality electrophotographic images over a long period of time. Also, at least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus that can form high-quality electrophotographic images over a long period of time. [Means for solving the problem]
[0009] According to at least one aspect of the present disclosure, A fixing device, a fixing film having an endless shape; a pressure member disposed opposite the fixing film and forming a nip with the fixing film; a heating member that is disposed inside the fixing film, has a surface facing an inner circumferential surface of the fixing film, and biases the fixing film against the pressure member; Fluorine grease is interposed between the inner circumferential surface and the opposing surface, The fixing film has at least a base layer, an elastic layer, and a surface layer in this order, The surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), The surface layer contains a plurality of spherulites of the PFA, The fixing device provides a fixing material having an endothermic curve in which a sample taken from the surface layer is used as a measurement sample and measured at a temperature rise rate of 20°C / min using a differential scanning calorimeter (DSC), and the endothermic curve shows an amount of endothermic heat of 21 J / g or more during the temperature rise process. Effect of the Invention
[0010] According to at least one aspect of the present disclosure, it is possible to obtain a fixing device that contributes to the formation of high-quality electrophotographic images over a long period of time. Also, according to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus that can form high-quality electrophotographic images over a long period of time. [Brief description of the drawings]
[0011] [Figure 1] Schematic diagram of an image forming apparatus according to one embodiment of the present disclosure. [Diagram 2] Schematic diagram of a fixing device according to one embodiment of the present disclosure. [Diagram 3] Schematic diagram of a fixing film according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower limit and the upper limit, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper limit and the lower limit of each numerical range can be arbitrarily combined. Hereinafter, the embodiment of the present disclosure will be described in detail. Note that the technical scope of the present disclosure is not limited to the following description.
[0013] <Configuration> A fixing device, a fixing film having an endless shape; A pressure section that is disposed opposite the fixing film and forms a nip with the fixing film. Materials and a heating member that is disposed inside the fixing film, has a surface facing an inner circumferential surface of the fixing film, and biases the fixing film against the pressure member; Fluorine grease is interposed between the inner circumferential surface and the opposing surface, The fixing film has at least a base layer, an elastic layer, and a surface layer in this order, The surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), The surface layer contains a plurality of spherulites of the PFA, A fixing device characterized in that, when a sample taken from the surface layer is used as a measurement sample and measured using a differential scanning calorimeter (DSC) at a heating rate of 20°C / min, the heat absorption curve during the heating process shows an amount of heat absorption of 21 J / g or more.
[0014] <Electrophotographic image forming apparatus> 1 is a cross-sectional view of a color electrophotographic printer, which is an example of an electrophotographic image forming apparatus (hereinafter also referred to as an "image forming apparatus") according to the present embodiment, taken along a sheet conveying direction. In this embodiment, the color electrophotographic printer is simply referred to as a "printer."
[0015] The printer 1 shown in FIG. 1 includes image forming units 10 for the colors Y (yellow), M (magenta), C (cyan), and Bk (black). The photosensitive drum 11 is pre-charged by a charger 12. Then, a latent image is formed on the photosensitive drum 11 by a laser scanner 13. The latent image is turned into a toner image by a developing unit 14. The toner image on the photosensitive drum 11 is sequentially transferred by a primary transfer blade 17 to an image carrier, for example, an intermediate transfer film 31. After transfer, the toner remaining on the photosensitive drum 11 is removed by a cleaner 15. As a result, the surface of the photosensitive drum 11 becomes clean and is prepared for the next image formation.
[0016] Meanwhile, recording material P is sent out one by one from paper feed cassette 20 or multi-paper feed tray 25 in the direction of arrow 3 to a pair of registration rollers 23. The pair of registration rollers 23 temporarily receives the recording material P and straightens it out if it is skewed. Then, the pair of registration rollers 23 synchronizes with the toner image on intermediate transfer film 31 and sends recording material P between intermediate transfer film 31 and secondary transfer roller 35. The color toner image on the intermediate transfer film is transferred onto recording material P by a transfer body such as secondary transfer roller 35. Thereafter, the toner image on the recording material is fixed onto the recording material by heating and pressurizing recording material P by fixing device 40.
[0017] The electrophotographic image forming apparatus includes a fixing device 40. Next, a description will be given of the fixing device in the electrophotographic image forming apparatus. Fig. 2 is a schematic diagram of the fixing device 40, which is an example of a film heating type heating device (tensionless type).
[0018] The fixing device has a fixing film having an endless shape, a pressure member arranged opposite the fixing film and forming a nip with the fixing film, and a heating member arranged inside the fixing film, having a surface facing the inner surface of the fixing film, and pressing the fixing film against the pressure member.
[0019] Reference numeral 43 denotes a ceramic heater (hereafter referred to as heater) as a heating element. The heater 43 is basically composed of a long, thin ceramic substrate with its longitudinal direction perpendicular to the drawing, and an energized heat generating resistor layer provided on the surface of the substrate. The heater 43 is a low-heat capacity heater that increases in temperature with a steep rise characteristic overall when electricity is applied to the heat generating resistor layer. It is also configured to switch the energized area depending on the longitudinal width size of the recording material.
[0020] The fixing film 41 is a cylindrical (endless) heat-resistant member that transmits heat. The fixing film 41 is a fixing member that is loosely fitted onto a support member including the heater 43. The fixing film 41 is as shown in Fig. 3, and is a fixing film having a three-layer composite structure of at least a surface layer 41a, an elastic layer 41c, and a base layer 41d.
[0021] The pressure roller 44 is a heat-resistant elastic pressure roller serving as a pressure member, and has a core and an elastic layer made of heat-resistant rubber such as silicone rubber or fluororubber, or a silicone rubber foam. Both ends of the core are rotatably supported by bearings. In other words, it is preferable that the pressure member is a pressure roller.
[0022] The fixing film 41 and heater 43 are arranged above the pressure roller 44 in parallel with the pressure roller 44 on the heater 43 side, and pressed by a pressing member (not shown). That is, the pressure roller is arranged facing the fixing film. Also, the heating member is arranged inside the fixing film, has a surface facing the inner circumferential surface of the fixing film (hereinafter also simply referred to as the facing surface), and presses the fixing film against the pressure member. In this way, the lower surface of the heater 43 and the upper surface of the pressure roller 44 are pressed against each other via the fixing film 41 against the elasticity of the roller elastic layer, forming a fixing nip portion of a predetermined width as a heating portion.
[0023] The pressure member is driven by, for example, a driving unit (not shown). By driving the pressure member, the fixing film is brought into a driven state in which it is driven by the pressure member. For example, the pressure roller 44 is driven to rotate at a predetermined peripheral speed in the counterclockwise direction indicated by the arrow by a driving means (not shown). A rotational force acts on the cylindrical fixing film 41 due to the frictional force between the pressure roller 44 and the fixing film 41 at the fixing nip portion caused by the rotational drive of the pressure roller 44. The fixing film 41 then comes into a driven rotation state in the clockwise direction indicated by the arrow while sliding in close contact with the downward surface of the heater 43. The support member 46 also serves as a rotation guide member for the cylindrical fixing film 41.
[0024] In this way, the fixing film 41 slides in close contact with the heater 43. At this time, in order to ensure the sliding property between the fixing film 41 and the heater 43, the fixing device has fluorine grease (not shown) on the surface of the heater. That is, fluorine grease is interposed between the inner peripheral surface of the fixing film and the opposing surface. It can also be said that fluorine grease is interposed between the heating body 43 and the fixing film in the fixing device. The fluorine grease acts as a lubricant. By using fluorine grease, it is possible to maintain lubricity for a long period of time even under conditions of contact with a heater heated to a high temperature. The fluorine grease is not particularly limited, and known fluorine greases can be used. Examples of fluorine greases include those containing fluorine resin particles and fluorine oil. The fluorine resin contained in the fluorine grease has the function of increasing the retention of the fluorine oil in the grease by swelling the fluorine oil. Examples of the fluorine oil include PFPE and HFE. Examples of the fluorine resin include PTFE, PFA, and FEP. As a commercially available product, for example, MOLYKOTE HP-300 grease (manufactured by DuPont Co., Ltd.) can be used.
[0025] The pressure roller 44 is driven to rotate, and the cylindrical fixing film 41 is rotated accordingly, and the heater 43 is energized, so that the heater is heated quickly to a predetermined temperature and is in a temperature-regulated state. In this state, the recording material P carrying the unfixed toner image T is introduced between the fixing film 41 and the pressure roller 44 in the fixing nip. Then, in the fixing nip, the toner image-carrying side of the recording material P is in close contact with the outer surface of the fixing film 41, and the recording material P is sandwiched and transported to the fixing nip together with the fixing film 41. During this sandwiching and transporting process, the recording material P is heated by the heat of the fixing film 41 heated by the heater 43, and the unfixed toner image T on the recording material P is heated and pressed onto the recording material P, so that it is melted and fixed. The recording material P that has passed through the fixing nip is separated from the surface of the fixing film 41 by curvature and transported to be discharged.
[0026] Reference numeral 45 denotes a contact thermometer (thermistor) that measures the temperature of the fixing film 41 heated by the heater 43 and passes the detection result to a temperature control means (not shown). Reference numeral 46 denotes a heater holder, which is a member that holds the heater 43 that has been heated to a high temperature.
[0027] Next, the fixing film that constitutes a part of the fixing device of the present disclosure will be described in detail. The fixing film according to one embodiment of the present disclosure has at least a base layer, an elastic layer, and a surface layer in this order. That is, the fixing film has a base layer, an elastic layer on the base layer, and a surface layer on the elastic layer. Other layers may be provided between the base layer, the elastic layer, and the surface layer, and on the inner peripheral surface side of the base layer and the outer peripheral surface side of the surface layer, as necessary. The fixing film may have an endless shape.
[0028] The fixing film 41 may have a configuration as shown in Fig. 3. For example, in Fig. 3, the fixing film has a base layer 41d, an elastic layer 41c covering the outer surface of the base layer, and a surface layer 41a covering the surface of the elastic layer opposite to the side facing the base layer. The surface layer 41a may have a resin layer 41b as an adhesive layer on the surface of the elastic layer 41c opposite to the side facing the base layer.
[0029] Each layer will now be described in detail. (1) Base layer The material of the base layer 41d is not particularly limited, and any known material used for a base layer may be used. For example, metals and alloys such as aluminum, iron, stainless steel (SUS), and nickel, as well as heat-resistant resins such as polyimide, are used. Stainless steel is preferable. The thickness of the base layer 41d is not particularly limited, but is preferably 20 μm or more and 100 μm or less, and more preferably 20 μm or more and 50 μm or less, from the viewpoints of strength, flexibility, and heat capacity.
[0030] The outer surface of the base layer 41d may be subjected to a surface treatment to impart adhesion to the elastic layer 41c. The surface treatment may be one or a combination of physical treatments such as blasting, lapping, and polishing, and chemical treatments such as oxidation, coupling agent, and primer treatment.
[0031] When the elastic layer 41c containing silicone rubber is provided on the surface of the base layer 41d, it is preferable to perform a primer treatment on the surface of the base layer 41d in order to improve the adhesion between the base layer 41d and the elastic layer 41c. Examples of the primer used in the primer treatment include paints in which a silane coupling agent, a silicone polymer, hydrogenated methylsiloxane, an alkoxysilane, a reaction accelerating catalyst, and a coloring agent such as red iron oxide are appropriately mixed and dispersed in an organic solvent.
[0032] The primer can be appropriately selected depending on the material of the base layer 41d, the type of the elastic layer 41c, or the form of the crosslinking reaction. In particular, when the elastic layer 41c contains a large amount of unsaturated aliphatic groups, a primer containing a hydrosilyl group is preferably used to impart adhesiveness by reacting with the unsaturated aliphatic groups. When the elastic layer 41c contains a large amount of hydrosilyl groups, a primer containing an unsaturated aliphatic group is preferably used.
[0033] Other examples of the primer include those containing an alkoxy group. A commercially available primer can be used. The primer treatment includes a step of applying the primer to the outer surface of the base layer 41d (the surface to be bonded to the elastic layer 41c) and drying or baking the primer.
[0034] (2) Elastic layer The material of the elastic layer 41c is not particularly limited, and a known material used as an elastic layer of a fixing film can be adopted. The elastic layer 41c preferably contains silicone rubber having excellent heat resistance. In addition, as a raw material of the silicone rubber, an addition curing type liquid silicone rubber is preferably used. The elastic layer 41c can be formed, for example, by applying an addition curing type liquid silicone rubber to the outer surface of the base layer 41d and curing it by heating. The application method is not particularly limited, and a known method may be used.
[0035] The thickness of the elastic layer 41c can be appropriately designed in consideration of the surface hardness of the fixing film and the width of the fixing nip portion to be formed. The thickness of the elastic layer is preferably 100 μm to 1000 μm, more preferably 150 μm to 350 μm. By setting the thickness of the elastic layer within this range, a sufficient width of the fixing nip portion can be ensured when the fixing film is incorporated into a fixing device.
[0036] As the silicone rubber, for example, a cured product of an addition curing type liquid silicone rubber mixture described later can be used. The elastic layer 41c can be formed by applying and heating the liquid silicone rubber mixture by a known method.
[0037] The liquid silicone rubber mixture typically contains the following components (a) to (d): Component (a): an organopolysiloxane having an unsaturated aliphatic group; Component (b): an organopolysiloxane having active hydrogen bonded to silicon; Component (c): catalyst; Component (d): Thermally conductive filler Each component will be described below.
[0038] Component (a) The organopolysiloxane having an unsaturated aliphatic group is an organopolysiloxane having an unsaturated aliphatic group such as a vinyl group, and examples thereof include those represented by the following formulas (1) and (2). The organopolysiloxane having an unsaturated aliphatic group is preferably a linear type. [ka]
[0039] In formula (1), m 1 is an integer equal to or greater than 0, and n 1 represents an integer of 3 or more. In addition, in the structural formula (1), R 1 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 1 At least one of R represents a methyl group. 2 each independently represents an unsaturated aliphatic group. [ka]
[0040] In formula (2), n 2 denotes a positive integer, and R 3 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group, provided that R 3 At least one of R represents a methyl group. 4 each independently represents an unsaturated aliphatic group.
[0041] In formulas (1) and (2), R 1 and R 3 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by include the following groups. Unsubstituted hydrocarbon groups Alkyl groups (eg, methyl, ethyl, propyl, butyl, pentyl, hexyl). Aryl groups (eg, phenyl groups). Substituted hydrocarbon groups Substituted alkyl groups (eg, chloromethyl, 3-chloropropyl, 3,3,3-trifluoropropyl, 3-cyanopropyl, 3-methoxypropyl).
[0042] The organopolysiloxanes represented by formulas (1) and (2) have at least one methyl group directly bonded to the silicon atom forming the chain structure. However, for ease of synthesis and handling, R 1 and R 3 It is preferable that 50% or more of each group are methyl groups, and all of R 1 and R 3 More preferably, is a methyl group.
[0043] In addition, in formulas (1) and (2), R 2 and R 4Examples of the unsaturated aliphatic group that can be represented by include the following groups. That is, examples of the unsaturated aliphatic group include a vinyl group, an allyl group, a 3-butenyl group, a 4-pentenyl group, and a 5-hexenyl group. Among these groups, R 2 and R 4 is preferably a vinyl group.
[0044] From the viewpoint of moldability, the viscosity of component (a) is 1000mm 2 / s or more 50000mm 2 / s or less is preferable. 2 If the hardness is lower than 50,000 mm / s, it becomes difficult to adjust the hardness required for the elastic layer 20c. 2 If the viscosity is higher than 1 / s, the mixture will become too viscous and coating will become difficult. Viscosity (kinetic viscosity) can be measured using a capillary viscometer or rotational viscometer in accordance with JIS Z 8803:2011.
[0045] The blending amount of component (a) is preferably 55% by volume or more from the viewpoint of durability and 65% by volume or less from the viewpoint of heat conductivity, based on the liquid silicone rubber mixture used to form the elastic layer 20c.
[0046] Ingredient (b) The organopolysiloxane having active silicon-bonded hydrogens functions as a crosslinker that reacts with the unsaturated aliphatic groups of component (a) in the presence of a catalyst to form a cured silicone rubber. Any organopolysiloxane having a Si-H bond can be used as component (b). In particular, from the viewpoint of reactivity with the unsaturated aliphatic group of component (a), it is preferable to use one having an average of 3 or more hydrogen atoms bonded to silicon atoms in one molecule.
[0047] Specific examples of component (b) include the linear organopolysiloxane shown in the following formula (3) and the cyclic organopolysiloxane shown in the following formula (4). [ka]
[0048] In formula (3), m 2 is an integer equal to or greater than 0, and n 3 indicates an integer of 3 or more, and R 5 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group. [ka]
[0049] In formula (4), m 3 is an integer equal to or greater than 0, and n 4 indicates an integer of 3 or more, and R 6 each independently represents a monovalent unsubstituted or substituted hydrocarbon group that does not contain an unsaturated aliphatic group.
[0050] R in formulas (3) and (4) 5 and R 6 Examples of the monovalent unsubstituted or substituted hydrocarbon group not containing an unsaturated aliphatic group that can be represented by R 1 Among these, R 5 and R 6 It is preferable that 50% or more of each group are methyl groups, and all of R 5 and R 6 More preferably, is a methyl group.
[0051] Ingredient (c) The catalyst used in forming the silicone rubber may be, for example, a hydrosilylation catalyst for promoting the curing reaction. As the hydrosilylation catalyst, for example, a known substance such as a platinum compound or a rhodium compound may be used. The amount of the catalyst to be added may be appropriately set and is not particularly limited.
[0052] Ingredient (d) The elastic layer 41c may contain a filler. The filler is added to control the thermal conductivity, heat resistance, and elastic modulus. Examples of the thermally conductive filler include metals, metal compounds, and carbon fibers. Highly thermally conductive fillers are more preferable, and specific examples thereof include the following materials. Silicon metal (Si), silicon carbide (SiC), silicon nitride (Si3N4), boron nitride (BN), aluminum nitride (AlN), alumina (Al2O3), iron oxide (Fe2O3), zinc oxide (ZnO), magnesium oxide (MgO), titanium oxide (TiO2), silica (SiO2), copper (Cu), aluminum (Al), silver (Ag), iron (Fe), nickel (Ni), carbon black (C), carbon nanotubes (C), vapor grown carbon fiber, PAN (polyacrylonitrile) carbon fiber, pitch-based carbon fiber.
[0053] The elastic layer may also contain a reaction control agent (inhibitor). By containing a reaction control agent, the reaction start time can be controlled. The reaction control agent is not particularly limited and may be any known substance. Examples of the usable organic solvent include methylvinyltetrasiloxane, acetylene alcohols, siloxane-modified acetylene alcohols, and hydroperoxides.
[0054] (3) Resin layer The resin layer 41b is preferably capable of bonding the surface layer and the elastic layer, and preferably includes, for example, a cured product of an adhesive. That is, the resin layer is preferably an adhesive layer. The adhesive may be a solution type adhesive or a hot melt type adhesive. The adhesive is not particularly limited, and any known adhesive can be used, but it is preferable to use a silicone rubber adhesive, and more preferable to use an addition curing type silicone rubber adhesive. When the elastic layer contains silicone rubber, the elastic layer also has an uncrosslinked component. In this case, by heating, the inner surface of the surface layer and the uncrosslinked component of the elastic layer react with the uncrosslinked component in the adhesive and bond, so that the surface layer and the elastic layer can be more firmly bonded. Examples of addition-curing silicone rubber adhesives include those having one or more functional groups selected from the group consisting of vinyl groups, SiH groups, and epoxy groups. When the adhesive has a vinyl group, it reacts with a SiH group that is an uncrosslinked component that may be contained in the elastic layer. When the adhesive has a SiH group, it reacts with a vinyl group that is an uncrosslinked component that may be contained in the elastic layer. When the adhesive has an epoxy group, the epoxy group opens a ring and becomes an OH group, which forms a hydrogen bond with an OH group that may be contained in the inner surface of the surface layer. Specifically, SE1819CV, which is a mixture of equal amounts of "liquid A" and "liquid B" manufactured by Dow Corning Toray Co., Ltd., can be mentioned.
[0055] (4) Surface layer The surface layer 41a contains a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) which is a fluororesin. PFA is a copolymer of perfluoroalkyl vinyl ether (PAVE) and tetrafluoroethylene (TFE). There are no particular limitations on the PFA, and any known PFA may be used. The copolymerization ratio (molar ratio) of perfluoroalkyl vinyl ether (PAVE) to tetrafluoroethylene (TFE) (PAVE / TFE) is preferably 99.5 / 0.5 to 95.0 / 5.0, and more preferably 99.0 / 1.0 to 95. 5 / 4.5 is more preferable. Commercially available PFA may be used. Specific examples include AP-230 (trade name, manufactured by Daikin Industries, Ltd.) and AP-231SH (trade name, manufactured by Daikin Industries, Ltd.), which is a PFA with a fully fluorinated end group. The PFA can be confirmed by, for example, the presence of a peak characteristic of polytetrafluoroethylene (PTFE) in the ATR spectrum of FT-IR, and the presence of a peak at 994 cm -1 This can be confirmed by checking for the presence of a small peak nearby. First, the characteristic peak of PTFE is 1200 cm -1 (CF2 antisymmetric stretching), 1150cm -1 (CF2 symmetric expansion and contraction), 640cm -1 (CF2 out-of-plane bending angle (wagging)), 555 cm -1 (CF2 in-plane angle (scissors)), 505 cm-1 (CF2 in-plane bending (locking)). Also, there is a characteristic of PFA, 994cm -1 The position of the peak at around 994 cm varies depending on the length of the carbon chain of the perfluoroalkyl vinyl ether moiety. -1 In the case of the perfluoroethoxy group, it appears at 1090 cm -1 In the case of the perfluoromethoxy group, it appears at 881 cm -1 Appears in.
[0056] The surface layer 41a containing PFA can be formed by applying a dispersion (water-based dispersion paint) or powder paint mainly composed of PFA to the surface of the elastic layer 41c, and then heating the coating to a temperature above its melting point to form a film. Alternatively, a PFA tube manufactured by extrusion molding can be used to cover the surface of the elastic layer 41c. The surface layer 41a is, for example, a PFA tube.
[0057] A sample taken from the surface layer 41a is used as a measurement sample, and an endothermic curve measured at a temperature rise rate of 20° C. / min using a differential scanning calorimeter (DSC) shows an endothermic amount of 21 J / g or more during the temperature rise process. Generally, the heating process in DSC measurement using a sampled sample as the measurement sample may be performed two or more times depending on the purpose of the measurement. When the heating process is performed two or more times, if the amount of heat absorbed in the first heating process is 21 J / g, it can be said to satisfy the above-mentioned "the amount of heat absorbed in the heating process is 21 J / g or more." Therefore, hereinafter, the "amount of heat absorbed in the heating process" may be referred to as the "amount of heat absorbed in the first heating process."
[0058] The amount of heat absorbed during the temperature rise process in DSC measurement is the amount of heat absorbed due to the crystalline melting of PFA. The degree of crystallinity of PFA can be calculated by dividing the amount of heat absorbed by the heat of complete crystalline melting of PFA (92.9 J / g). When the amount of heat absorbed is 21 J / g or more, the abrasion resistance to paper is good. When the amount of heat absorbed is 24 J / g or more, the abrasion resistance to paper is even better.
[0059] The upper limit of the heat absorption amount is not particularly limited, but is preferably 40 J / g or less, particularly 27 J / g or less. If the heat absorption amount is 40 J / g or less, a certain amount of amorphous PFA is contained in the surface layer, and it becomes easier to make the surface layer follow the deformation of the elastic layer better. The heat absorption amount during the temperature rise process is preferably 21 to 40 J / g, more preferably 21 to 27 J / g, and even more preferably 25 to 27 J / g. In addition, unless otherwise specified, the measurement of differential scanning calorimetry (DSC) and the analysis of DSC charts in this disclosure are in accordance with Japanese Industrial Standards (JIS) K7121-2012.
[0060] One method for achieving a heat absorption of 21 J / g or more is to heat the surface layer 41a to a temperature above the melting point of PFA after formation during the manufacturing process of the fixing member, and then promote crystallization of the PFA by controlling the cooling rate. Although the specific method is not particularly limited, the following methods for heat treatment of the surface layer can be used.
[0061] After the surface layer is formed, an upright cylindrical heating cylinder capable of heating up to, for example, 330°C or higher is used to heat the entire fixing film. A band heater equipped with a thermocouple is installed inside the heating cylinder to control the heating temperature of the fixing film. The heating temperature is preferably from the melting temperature of PFA to 350°C. The heating time may be any time that allows the surface layer to reach a desired temperature, and may be, for example, 1 to 20 minutes, 1 to 10 minutes, or 2 to 5 minutes.
[0062] After the heating is completed, the cooling rate of the heating cylinder is controlled to control the cooling rate of the fixing member. For example, the cooling rate can be controlled by providing an air supply nozzle on the outer periphery of the heating cylinder and adjusting the air flow rate. The slower the cooling rate in the crystallization temperature range of PFA, the more the crystallization of PFA can be promoted, and it is preferable to adjust the cooling rate so that the heat absorption amount is 21 J / g or more. It is preferable to control the cooling rate until the temperature of the surface layer falls below the crystallization temperature range of PFA. The cooling rate may be in a range that can be controlled to an endothermic amount of 21 J / g or more, and is not particularly limited, but is preferably 5 to 60°C / min, and more preferably 10 to 30°C / min.
[0063] The surface layer 41a preferably has a degree of orientation of PFA molecules in a direction perpendicular to the circumferential direction of the surface layer, as determined by a transmission X-ray diffraction method, of 35% or less, particularly 34% or less, and further preferably 25% or less. By having a degree of orientation of 35% or less, the fixing film can be Since the degree of orientation of the PFA molecules in the perpendicular direction is small, even if fluorine oil adheres, it is possible to more reliably suppress the infiltration of the fluorine oil in the direction perpendicular to the circumferential direction of the fixing film. As a result, it is possible to prevent chemical cracks from occurring along the direction for a long period of time. The lower limit of the degree of orientation is not particularly limited, but can be, for example, 0%. The preferred range of the degree of orientation is, for example, 0 to 35%, particularly 0 to 34%, and further 0 to 25%. The degree of orientation of the surface layer can be adjusted by adjusting the conditions during cylindrical molding of the fluororesin. The method for measuring the degree of orientation will be described later.
[0064] The surface layer 41a contains a plurality of PFA spherulites. When the surface layer 41a contains a plurality of PFA spherulites, the size of the spherulites becomes smaller, and the impregnation of the fluorine oil is reduced, so that chemical cracks are less likely to occur, and the durability against chemical cracks is improved. As a method for making the surface layer 41a contain a plurality of PFA spherulites, for example, a method of subjecting the surface layer to heat treatment can be mentioned. The presence of PFA spherulites can be confirmed by the method described below.
[0065] The number of PFA spherulites is not particularly limited as long as it is plural. For example, 2 When the molecular weight is within the above range, the durability against chemical cracking tends to be good. In addition, the spherulites of PFA were observed using a transmission polarizing microscope and were 2 The number of spherulites is determined by counting the number inside.
[0066] The thickness of the surface layer 41a is preferably 100 μm or less. The thickness of the surface layer is more preferably 10 to 100 μm, further preferably 10 to 70 μm, and particularly preferably 15 to 50 μm. By keeping the thickness within the above range, the abrasion resistance is improved. The thickness of the surface layer 41a can be measured using a micrometer.
[0067] As a method for achieving the above range, for example, the following method can be used. Here, an example is given in which a PFA tube is used to prepare the surface layer 41a, but the surface layer according to the present disclosure is not limited to being formed using a PFA tube.
[0068] The PFA tube can be produced, for example, by extruding molten PFA from a cylindrical die. Such a PFA tube is quenched during the extrusion process and crystallization proceeds rapidly, so the crystals are oriented in the extrusion direction and the crystallinity is low. After the PFA tube is coated on the surface of the elastic layer 41c to form the surface layer 41a, the surface layer is heated to increase the crystallinity and form spherulites on the surface of the surface layer. Increasing the crystallinity makes it easier to control the amount of heat absorption during the first heating process to within the above-mentioned range.
[0069] Heat treatment also relaxes the molecular orientation of the PFA tube, and the molecular chains that were oriented in the extrusion direction become random. This improves the thermal conductivity in the thickness direction. At this time, the degree of orientation of the PFA tube measured using transmission X-ray diffraction is 35% or less.
[0070] The adhesiveness of the inner surface of the surface layer 41a can be improved by previously performing a sodium treatment, an excimer laser treatment, an ammonia treatment, or a plasma etching treatment. It is preferable to treat the inner surface of the PFA tube using an excimer laser treatment.
[0071] For the excimer laser treatment, a compound that absorbs ultraviolet light is attached to the inner surface of the PFA tube, and then ultraviolet lasers such as KrF excimer laser light and ArF excimer laser light are used. It is preferable to irradiate the PFA tube with ultraviolet light. Known compounds that absorb ultraviolet light can be used. For example, an aqueous solution is prepared by mixing a compound that absorbs ultraviolet light, such as sodium benzoate, with a known fluorosurfactant, and the aqueous solution is applied to the inner surface of the PFA tube and allowed to dry naturally.
[0072] The irradiation conditions of the excimer laser beam are usually selected from the viewpoint of improving wettability and adhesiveness, and the dose per shot or the number of shots is adjusted. In the present disclosure, it is preferable to increase the number of shots more than is usually necessary to sufficiently carbonize the inner surface of the PFA tube. For example, the dose of the excimer laser beam is preferably 100 to 600 mJ / cm. 2 / pulse, more preferably 200-400mJ / cm 2 The number of shots is preferably 3 to 10, and more preferably 4 to 8.
[0073] The measurement methods for each physical property in the present disclosure are shown below. <Method for measuring endothermic heat> First, the surface layer is isolated from the fixing film. Specifically, the laminate of the elastic layer and the surface layer is peeled off from the substrate. The peeled off laminate of the elastic layer and the surface layer is immersed in e-Solv 21RS (manufactured by Kaneko Chemical Co., Ltd.), placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves are applied for 60 minutes to dissolve the elastic layer. Thereafter, the laminate was taken out, washed with water, wiped with toluene, and wiped with ethanol, so that only the surface layer could be isolated. The entire surface layer thus isolated was used as a sample.
[0074] The endothermic heat is measured using a differential scanning calorimeter (product name: Q2000, manufactured by TA Instruments). The melting points of indium and zinc are used for temperature correction of the detector of the device, and the heat of fusion of indium is used for heat correction. Specifically, 4 mg of the surface layer isolated as described above is precisely weighed and placed in an aluminum pan. An empty aluminum pan is used as a reference. The measurement is performed at a temperature increase rate of 20°C / min within a measurement range of 25°C to 400°C. The temperature is increased to 400°C and held for 5 minutes, and then decreased to 25°C at a temperature decrease rate of 20°C / min. At this time, the area enclosed by the temperature-endothermic heat curve including the endothermic peak and the baseline is taken as the endothermic heat.
[0075] <Method for measuring the number of spherulites> First, the surface layer is isolated from the fixing film as described above. The outer surface of the isolated surface layer is then observed with a polarizing microscope (ECLIPSE LV100N POL (Nikon Corporation)) to obtain an observation image of the spherulites. The observation conditions are that the fluororesin sample is taken out and the objective lenses of the polarizing microscope are 5x and 20x. By using a transmission polarizing microscope, it is possible to obtain an observation image that confirms the structure of the spherulites. From the obtained observation image of the spherulites, it is possible to confirm the number of spherulites and to confirm that the surface layer contains multiple PFA spherulites.
[0076] <Surface layer orientation measurement> First, the surface layer is isolated from the electrophotographic member. Specifically, a razor is inserted between the elastic layer and the base layer, and the laminate of the elastic layer and the surface layer is peeled off from the base layer. The peeled off laminate of the elastic layer and the surface layer is immersed in e-Solv 21RS (manufactured by Kaneko Chemical Co., Ltd.), placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves are applied for 60 minutes to dissolve the elastic layer. The laminate is then removed, washed with water, wiped with toluene, and wiped with ethanol, allowing only the surface layer to be isolated. The degree of orientation of the surface layer is calculated using wide-angle X-ray diffraction. Oriented samples have an intensity distribution along the Debye ring, and X-ray diffraction images are used to measure the degree of orientation. Using a fiber sample stage, 2θ is fixed to a peak near 18°, and the sample is rotated 360° (β rotation) to measure the intensity distribution along the Debye ring. From the obtained intensity distribution, the degree of orientation of the surface layer is calculated using the following formula. H = {(360-ΣW / 360)} × 100 In the formula, H represents the degree of orientation (%), and W represents the half-width. The half-width indicates the half-width of two peaks originating near 2θ=18°, namely, a peak appearing at a β rotation angle of 0 to 180° and a peak appearing at a β rotation angle of 180° to 360°. The X-ray diffraction apparatus used is a rotating anode type X-ray diffraction apparatus RINT2500 (X-ray: CuKα) manufactured by Rigaku Corporation, and the measurement is performed under the conditions of a tube voltage of 40 kV and a tube current of 15 mA.
[0077] <Method for measuring surface layer thickness> The surface layer thickness is measured using a high-precision digital micrometer (MDH-25MC, manufactured by Mitutoyo Corporation). The measurement result is the arithmetic average value of five points.
[0078] [Evaluation method] Next, the evaluation method in this example will be described.
[0079] (Rating 1: Durability against chemical cracks) The prepared fixing device was used for evaluation under the following conditions. Test environment: room temperature 10 degrees, humidity 10% Process speed: 280mm / sec Print speed: 60 pages / min Paper passing conditions: A grid image is formed on GF-C104 (manufactured by Nippon Paper Industries Co., Ltd., 105 g paper, A4 size), and the paper is passed continuously.
[0080] After each 100,000 sheets, GC-C081 (68g paper, A4 size, manufactured by Nippon Paper Industries Co., Ltd.) is passed through the paper, and the presence or absence of scratches in the longitudinal direction of the surface layer after the paper passing is checked and evaluated according to the following criteria. (Evaluation Criteria) Rank A: No scratches even after passing over 500,000 sheets Rank B: No scratches even after passing over 400,000 sheets Rank C: No scratches even after passing over 300,000 sheets Rank D: Scratches occur after less than 300,000 sheets
[0081] (Rating 2: Durability rating) <Abrasion resistance evaluation> The prepared fixing device was used for evaluation under the following conditions. Test environment: room temperature 25 degrees, humidity 50% Process speed: 280mm / sec Print speed: 60 pages / min Paper passing conditions: A grid image is printed on CS-068 (manufactured by Nippon Paper Industries Co., Ltd., 68g paper, A4 size). Forming and continuous feeding (Evaluation Criteria) A: Almost no wear on the surface layer is observed even after 500,000 sheets are passed through. B: Almost no wear on the surface layer is observed even after 200,000 sheets are passed, but slight wear on the surface layer due to the edge of the paper is observed after 500,000 sheets are passed. C: After 200,000 sheets are passed, slight wear of the surface layer due to the edge of the paper is observed, and after 500,000 sheets are passed, clear wear of the surface layer due to the edge of the paper is observed. D: After 200,000 sheets are passed, the surface layer is clearly worn away by the edges of the paper.
[0082] <Evaluation of motor torque current value> In addition to the evaluation of wear resistance, the motor torque current value is measured every 100,000 sheets and judged according to the following evaluation criteria. indicates that the grease has excellent heat resistance. (Evaluation Criteria) Rank A: Motor torque less than 2.0A Rank B: Motor torque 2.0 or more and less than 2.5A Rank C: Motor torque 2.5 or more and less than 3.0A Rank D: Motor torque 3.0A or more EXAMPLES
[0083] The present disclosure will be described in more detail below using examples and comparative examples, but the aspects of the present disclosure are not limited thereto.
[0084] <Example 1> (Method of manufacturing fixing film) In this example, a fixing film as shown in FIG. 3 was prepared.
[0085] (Inner surface treatment of PFA tube) Neoflon PFA: A PFA tube with a thickness of 20 μm obtained by extrusion molding using AP-231SH (manufactured by Daikin Industries, Ltd.) as the raw material was used. An aqueous solution containing 5% by mass of sodium benzoate and 1% by mass of Surflon S-113 (a fluorosurfactant manufactured by AGC Seimi Chemical Co., Ltd.) was applied to the entire inner surface of the PFA tube, which was then naturally dried and subjected to 300 mJ / cm2. 2 The tube was irradiated with six shots of KrF excimer laser light of 1 / 1000 s.p.p. to obtain a PFA tube with a treated inner surface.
[0086] (base layer) The base layer was made of SUS with an inner diameter of 24 mm and a thickness of 30 μm.
[0087] (Formation of inner sliding layer) First, an aromatic tetracarboxylic dianhydride or its derivative and an aromatic diamine in approximately equimolar amounts were reacted in an aprotic polar organic solvent to obtain a polyimide precursor solution. The obtained polyimide precursor solution was applied to the inner circumferential surface of the base layer by a ring coating method, and after drying the solvent in an electric furnace, the resultant was heated at 260 to 400°C for about 1 hour to form an inner sliding layer. The thickness of the inner sliding layer was set to 12 μm.
[0088] (Formation of primer layer and elastic layer) A primer layer and an elastic layer were formed on the base layer on which the inner sliding layer was formed by the following procedure. A hydrosilyl silicone primer (DY39-051 A / B; Dow Toray) was applied onto the base layer and cured by heating for 5 minutes at 200° C. A liquid addition-curing silicone rubber mixture containing the following components (a) to (d) was applied onto the primer layer to a thickness of 250 μm and cured by heating for 30 minutes at 200° C. to form a silicone rubber elastic layer with a thickness of 250 μm.
[0089] (Silicone rubber mixture) Component (a): Linear organopolysiloxane having an unsaturated aliphatic group Component (b): Organopolysiloxane having active hydrogen bonded to silicon Component (c): Catalyst Component (d): Thermally conductive filler
[0090] First, 100 parts by mass of a silicone polymer having vinyl groups, which are unsaturated aliphatic groups, only at both ends of the molecular chain and having methyl groups as unsubstituted hydrocarbon groups containing no other unsaturated aliphatic groups, was prepared as component (a). Manufactured by Lest, viscosity 5000mm 2 / s) will be referred to as "Vi" from here on. Next, 370 parts by mass of alumina (product name: Amina Beads CB-P10, manufactured by Showa Denko K.K.) was added to this Vi as component (d), and the mixture was placed in a planetary mixer (Thinky Corporation, ARV-5000) and stirred and mixed at 600 rpm for 2 minutes to obtain mixture 1.
[0091] Next, 0.2 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Tokyo Chemical Industry Co., Ltd.), which is a cure retarder, was dissolved in the same mass of toluene and added to the mixture 1 to obtain a mixture 2. Next, 0.1 parts by mass of a hydrosilylation catalyst (platinum catalyst: a mixture of 1,3-divinyltetramethyldisiloxane platinum complex, 1,3-divinyltetramethyldisiloxane, and 2-propanol) as component (c) was added to mixture 2 to obtain mixture 3. Furthermore, as component (b), a silicone polymer having a linear siloxane skeleton and having active hydrogen groups bonded to silicon only on the side chain (product name: HMS-301, manufactured by Gelest, viscosity 30 mm 2 1.1 parts by mass of 1.2 parts by mass of 1.2-hexanediaminetetraacetate (hereinafter referred to as "SiH") was weighed out. This was added to mixture 3 and mixed thoroughly to obtain a liquid addition-curing silicone rubber mixture.
[0092] (Applying adhesive layer) After forming the elastic layer, an adhesive (SE1819CV) is applied to the elastic layer using the ring coating method. A / B (manufactured by Dow Toray) was applied to a thickness of 7 μm.
[0093] (Formation of surface layer) After the adhesive was applied, the PFA tube, which had been subjected to the above-mentioned inner surface treatment, was covered on the adhesive by a method of vacuum expanding and covering from the outside (vacuum expansion covering method) to form a surface layer. Specifically, the PFA tube was attached under vacuum to the inner surface of an outer cylinder with an inner diameter larger than the outer diameter of the workpiece after the adhesive was applied and the elastic layer was formed, and the PFA tube was expanded in diameter, and the workpiece was inserted into it, and then the vacuum was released to cover the adhesive. After removing excess adhesive and air between the PFA tube and the elastic layer with an O-ring or the like, the adhesive was cured and bonded using a heating means such as an electric furnace to form a resin layer. Specifically, the workpiece was heated at 200°C for 5 minutes using a high-temperature electric furnace (Perfect Oven PHH-201M (Espec Corp.)). Then, both ends were cut to the desired length (350 mm).
[0094] (Heat treatment of surface layer) After cutting both ends to the desired length, the piece was inserted into a heating cylinder with an inner diameter of φ42 mm, and the entire area was heat-treated by a band heater inside the heating cylinder. The heating temperature was 330°C, and the heat treatment was performed so that the actual temperature of the surface layer was equal to or higher than the melting temperature of PFA.
[0095] The heating time was set to 3 minutes after the fixing film was placed in the heating cylinder, which was the time required for the surface layer's actual temperature to reach the desired heat treatment temperature. After 3 minutes had passed since the film was placed in the heating cylinder, the heating cylinder was cooled to 200°C at a rate of 20°C / min. The film was then taken out of the heating cylinder into a room temperature (25°C) atmosphere to obtain a fixing film. The physical properties of the prepared fixing film are shown in Table 1.
[0096] The obtained fixing film was used to produce the fixing device shown in Fig. 2. Here, fluorine grease (product name: MOLYKOTE HP-300 Grease; manufactured by DuPont Co., Ltd.) was applied to the inner surface of the base layer 41d, so that the surface of the heater 43 of the fixing device was provided with fluorine grease (not shown). Here, "MOLYKOTE HP-300 Grease" is a mixture of fluorine oil and PTFE particles as a thickener. The fixing film and the fixing device thus prepared were evaluated as follows, and the results are shown in Table 2.
[0097] <Method for measuring endothermic heat> First, the surface layer was isolated from the fixing film. Specifically, the laminate of the elastic layer and the surface layer was peeled off from the substrate. The peeled off laminate of the elastic layer and the surface layer was immersed in a silicone dissolving agent (product name: e-solv 21RS; manufactured by Kaneko Chemical Co., Ltd.), placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves were applied for 60 minutes to dissolve the elastic layer. Thereafter, the laminate was taken out, washed with water, wiped with toluene, and wiped with ethanol, and only the surface layer was isolated. The entire surface layer isolated was used as a sample.
[0098] The endothermic heat was measured using a differential scanning calorimeter (product name: Q2000, manufactured by TA Instruments). The melting points of indium and zinc were used for temperature correction of the detector of the device, and the heat of fusion of indium was used for heat correction. Specifically, 4 mg of the surface layer isolated as described above was precisely weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference. The measurement was performed at a temperature increase rate of 20°C / min within a measurement range of 25°C to 400°C. The temperature was increased to 400°C and held for 5 minutes, and then the temperature was decreased to 25°C at a rate of 20°C / min. At this time, the area surrounded by the temperature-endothermic heat curve including the endothermic peak and the baseline was taken as the endothermic heat.
[0099] <Method for measuring the number of spherulites> First, the surface layer was isolated from the fixing film as described above. The outer surface of the isolated surface layer was observed with a polarizing microscope (product name: ECLIPSE LV100N POL; manufactured by Nikon Corporation) to obtain an observation image of the spherulites. The observation was performed using a polarizing microscope with objective lenses of 5x and 20x magnification for the fluororesin sample. The number of spherulites was confirmed from the obtained observation image, and it was confirmed that the surface layer contained multiple PFA spherulites.
[0100] <Surface layer orientation measurement> First, the surface layer was isolated from the electrophotographic member. Specifically, a razor was inserted between the elastic layer and the base layer, and the laminate of the elastic layer and the surface layer was peeled off from the base layer. The peeled off laminate of the elastic layer and the surface layer was immersed in a silicone dissolving agent (product name: e-solv 21RS; manufactured by Kaneko Chemical Co., Ltd.), placed in a water tank of an ultrasonic cleaning device (product name: Bransonic (model 2510J-DTH); manufactured by Emerson Japan Co., Ltd.), and ultrasonic waves were applied for 60 minutes to dissolve the elastic layer. Thereafter, the laminate was taken out, washed with water, wiped with toluene, and wiped with ethanol to isolate only the surface layer. The orientation degree of the surface layer was calculated by wide-angle X-ray diffraction. X-ray diffraction images were used to measure the orientation degree. Using a fiber sample stage, 2θ was fixed at a peak near 18°, and the sample was rotated 360° (β rotation) to measure the intensity distribution along the Debye ring. From the obtained intensity distribution, the orientation degree of the surface layer was calculated using the following formula. H = {(360-ΣW / 360)} × 100 In the formula, H represents the degree of orientation (%), and W represents the half-width. The half-width indicates the half-width of two peaks originating near 2θ=18°, namely, a peak appearing at a β rotation angle of 0 to 180° and a peak appearing at a β rotation angle of 180° to 360°. The X-ray diffraction apparatus used was a rotating anode type X-ray diffraction apparatus RINT2500 (X-ray: CuKα) manufactured by Rigaku Corporation, and measurements were performed under conditions of a tube voltage of 40 kV and a tube current of 15 mA.
[0101] <Method for measuring surface layer thickness> The surface layer thickness was measured using a high-precision digital micrometer (MDH-25MC, manufactured by Mitutoyo Corporation), and the measurement results were the arithmetic mean value of measurements at five points.
[0102] [Evaluation method] Next, the evaluation method in this example will be described.
[0103] (Rating 1: Durability against chemical cracks) The prepared fixing device was used for evaluation under the following conditions. Test environment: room temperature 10 degrees, humidity 10% Process speed: 280mm / sec Print speed: 60 pages / min Paper passing conditions: A grid image was formed on copy paper (product name: GF-C104; Nippon Paper Industries Co., Ltd., 105g paper, A4 size) and the paper was passed continuously.
[0104] After every 100,000 sheets, a piece of copy paper (product name: GC-C081; manufactured by Nippon Paper Industries Co., Ltd., 68g paper, A4 size) was passed through the test piece, and the presence or absence of scratches (chemical cracks) in the longitudinal direction of the surface layer was checked and evaluated according to the following criteria. (Evaluation Criteria) Rank A: No chemical cracks were observed on the surface layer even after 500,000 sheets were passed through. Rank B: The number of sheets at which the occurrence of chemical cracks in the surface layer was first confirmed was 400,000 or more and less than 500,000. Rank C: The number of sheets at which the occurrence of chemical cracks in the surface layer was first confirmed was 300,000 or more and less than 400,000. Rank D: The number of sheets passed at which the occurrence of chemical cracks in the surface layer was first confirmed was less than 300,000 sheets.
[0105] (Rating 2: Durability rating) <Abrasion resistance evaluation> The prepared fixing device was used to carry out an abrasion resistance test under the following conditions, and was evaluated according to the following criteria. conditions Test environment: room temperature 25 degrees, humidity 50% Process speed: 280mm / sec Print speed: 60 pages / min Paper passing conditions: A grid image was formed on copy paper (product name: CS-068; Nippon Paper Industries Co., Ltd., 68g paper, A4 size) and the paper was passed continuously. (Evaluation Criteria) A: No wear was observed on the surface layer even after 500,000 sheets were passed through. B: No wear of the surface layer was observed even after 200,000 sheets were passed, but slight wear of the surface layer due to the edges of the paper was observed after 500,000 sheets were passed. C: After 200,000 sheets were passed, slight wear of the surface layer due to the edges of the paper was observed. After 500,000 sheets were passed, clear wear of the surface layer due to the edges of the paper was observed. D: After 200,000 sheets were passed, clear wear of the surface layer due to the edges of the paper was observed.
[0106] <Evaluation of motor torque current value> In addition to the evaluation of wear resistance, the motor torque current value was measured every 100,000 sheets and was evaluated according to the following criteria: A small motor torque current value indicates that the grease has excellent heat resistance. (Evaluation Criteria) Rank A: Motor torque less than 2.0A Rank B: Motor torque 2.0 or more and less than 2.5A Rank C: Motor torque 2.5 or more and less than 3.0A Rank D: Motor torque 3.0A or more
[0107] <Example 2> In the heat treatment of the surface layer, the cooling rate of the heating barrel was changed to 60°C / min. A fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0108] <Example 3> A fixing film was obtained in the same manner as in Example 1, except that in the heat treatment of the surface layer, the heating control temperature of the heating barrel was changed to 320° C. A fixing device was produced using the obtained fixing film.
[0109] <Example 4> Except for changing the thickness of the surface layer to 10 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0110] <Example 5> Except for changing the thickness of the surface layer to 100 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0111] <Example 6> A fixing film was obtained in the same manner as in Example 1, except that in the heat treatment of the surface layer, the cooling rate of the heating barrel was changed to a rate of 10° C. / min. A fixing device was produced using the obtained fixing film.
[0112] <Example 7> Except for changing the thickness of the surface layer to 5 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0113] <Example 8> Except for changing the thickness of the surface layer to 110 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0114] <Example 9> Except for changing the thickness of the surface layer to 5 μm, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0115] <Comparative Example 1> Except for not carrying out the heat treatment of the surface layer, a fixing film was obtained in the same manner as in Example 1. A fixing device was produced using the obtained fixing film.
[0116] <Comparative Example 2> A fixing film was obtained in the same manner as in Example 1, except that in the heat treatment of the surface layer, the cooling rate of the heating barrel was changed to 70° C. / min. A fixing device was produced using the obtained fixing film.
[0117] <Comparative Example 3> A fixing device was produced in the same manner as in Example 1, except that silicone grease (product name: G-501, manufactured by Shin-Etsu Silicones Co., Ltd.) was used instead of the fluorine grease.
[0118] <Comparative Example 4> The fixing was performed in the same manner as in Example 1, except that "959HP-PLUS" (product name, manufactured by Chemours Co., Ltd.) was used as the raw material for the surface layer instead of "AP-231SH" and silicone grease G-501 (manufactured by Shin-Etsu Silicones Co., Ltd.) was used instead of the fluorine grease. A film and fixing apparatus were prepared.
[0119] The results of Examples 1 to 9 and Comparative Examples 1 to 4 are summarized in Tables 1 and 2. [Table 1] [Table 2]
[0120] The fixing device manufactured by the method described in this embodiment was able to achieve both wear resistance and durability against chemical cracks.
[0121] The present disclosure relates to the following configurations. [Configuration 1] A fixing device, a fixing film having an endless shape; a pressure member disposed opposite the fixing film and forming a nip with the fixing film; a heating member that is disposed inside the fixing film, has a surface facing an inner circumferential surface of the fixing film, and biases the fixing film against the pressure member; Fluorine grease is interposed between the inner circumferential surface and the opposing surface, The fixing film has at least a base layer, an elastic layer, and a surface layer in this order, The surface layer comprises a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), The surface layer contains a plurality of spherulites of the PFA, A fixing device characterized in that, when a sample taken from the surface layer is used as a measurement sample and measured using a differential scanning calorimeter (DSC) at a heating rate of 20°C / min, the heat absorption curve during the heating process shows an amount of heat absorption of 21 J / g or more. [Configuration 2] The fixing device according to configuration 1, wherein the amount of heat absorbed during the temperature rise process is 40 J / g or less. 3. The fixing device according to configuration 1 or 2, wherein the degree of orientation of the PFA molecules in the direction perpendicular to the circumferential direction of the surface layer, as measured using a transmission X-ray diffraction method, is 35% or less. [Configuration 4] The fixing device according to any one of Configurations 1 to 3, wherein the surface layer has a thickness of 10 to 100 μm. [Configuration 5] 5. The fixing device according to any one of configurations 1 to 4, wherein the fluorine grease contains fluorine resin particles and fluorine oil. [Configuration 6] An electrophotographic image forming apparatus comprising the fixing device according to any one of the first to fifth aspects. [Explanation of symbols]
[0122] 10: image forming unit, 11: photosensitive drum, 12: charger, 13: laser scanner, 14: developer, 15: cleaner, 17: primary transfer blade, 20: paper feed cassette, 25: multi-paper feed tray, 23: registration roller pair, 31: intermediate transfer film, 35: secondary transfer roller, 40: fixing unit, 41: fixing film, 41a: surface layer, 41b: resin layer, 41c: elastic layer, 41d: base layer, 43: heating element, 44: pressure roller, 45: contact thermistor, 46: heater holder, P: recording material, T: toner
Claims
1. A fixing device, a fixing film having an endless shape; a pressure member disposed opposite the fixing film and forming a nip with the fixing film; a heating member that is disposed inside the fixing film, has a surface facing an inner circumferential surface of the fixing film, and biases the fixing film against the pressure member; Fluorine grease is interposed between the inner circumferential surface and the opposing surface, The fixing film has at least a base layer, an elastic layer, and a surface layer in this order, The surface layer contains a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), The surface layer contains a plurality of spherulites of the PFA, A fixing device characterized in that, when a sample taken from the surface layer is used as a measurement sample and a heat absorption curve is measured using a differential scanning calorimeter (DSC) at a heating rate of 20°C / min, the heat absorption amount during the heating process is 21 J / g or more.
2. 2. The fixing device according to claim 1, wherein the amount of heat absorbed during the temperature rise process is 40 J / g or less.
3. 2. The fixing device according to claim 1, wherein the degree of orientation of the PFA molecules in the surface layer in a direction perpendicular to the circumferential direction, as determined by a transmission X-ray diffraction method, is 35% or less.
4. 2. The fixing device according to claim 1, wherein the surface layer has a thickness of 10 to 100 μm.
5. The fixing device according to claim 1 , wherein the fluorine grease contains fluorine resin particles and fluorine oil.
6. 6. An electrophotographic image forming apparatus comprising the fixing device according to claim 1.
Citation Information
Patent Citations
Image forming device
JP1988313182A
Image heat fixing device
JP1990157878A
Lubricant composition and image fixing device using same
JP2005084225A
Image-fixing device
JP2007187889A
Cited By
Fixing member, fixing device, and image forming apparatus
JP2026126963A
Fixing member, fixing device, and image forming apparatus
JP7927892B2
Fixing member, fixing device, and image forming apparatus
WO2026160463A1